CONSISTENCY DEPENDENT NATURE OF SLIDING DEFORMATION IN SWELLING SOILS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The work is devoted to the changes in the nature of sliding deformation in swelling soils, depending on the change in soil consistency. Slip resistance tests were performed with both single-plane shear test rigs and torsion test rigs. At a soft plastic consistency, there is no peak sliding resistance in the constant speed sliding displacement test. Torsion tests show that in the case of soft plastic soils, sliding deformation occurs along the entire height of the test specimen without localization of the deformation and the formation of a displacement surface. In the case of overconsolidated clay soil, in the case of a constant velocity uniplane shear test, the dependence of the shear stress-shear strain is extreme, the shear resistance reaches a peak value. Then, during further displacement, the sliding resistance decreases to reach the minimum residual sliding resistance value. During the sliding test, when the deformations reach a certain critical size, deformation localization occurs, a localization zone is formed, after which the upper part of the sample moves relative to the lower stationary layer. Moreover, both the upper and lower parts are not subject to sliding deformations.
Keywords: argillaceous clays; swelling soils; swelling-shrinking; swelling deformations; sliding resistance; torsion method